Mice lacking circadian clock components display different mood-related behaviors and do not respond uniformly to chronic lithium treatment. (14th September 2015) - Schnell, Anna; Sandrelli, Federica; Ranc, Vaclav; Ripperger, Jürgen A.; Brai, Emanuele; Alberi, Lavinia; Rainer, Gregor; Albrecht, Urs
Abstract : Genomic studies suggest an association of circadian clock genes with bipolar disorder (BD) and lithium response in humans. Therefore, we tested mice mutant in various clock genes before and after lithium treatment in the forced swim test (FST), a rodent behavioral test used for evaluation of depressive-like states. We find that expression of circadian clock components, including Per2, Cry1 and Rev-erbα, is affected by lithium treatment, and thus, these clock components may contribute to the beneficial effects of lithium therapy. In particular, we observed that Cry1 is important at specific times of the day to transmit lithium-mediated effects. Interestingly, the pathways involving Per2 and Cry1, which regulate the behavior in the FST and the response to lithium, are distinct as evidenced by the phosphorylation of GSK3β after lithium treatment and the modulation of dopamine levels in the striatum. Furthermore, we observed the co-existence of depressive and mania-like symptoms in Cry1 knock-out mice, which resembles the so-called mixed state seen in BD patients. Taken together our results strengthen the concept that a defective circadian timing system may impact directly or indirectly on mood-related behaviors.